PENGARUH TEMPERATUR CETAKAN TERHADAP STRUKTUR MIKRO DAN KEKERASAN PISTON HASIL PENGECORAN MENGGUNAKAN 3D PRINTING - Devi Andriani; Wahyono Suprapto; Yudy Surya Irawan; Alfeus Sunarso (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2023)
Motorcycle users in 2019 reached 133,617,012 units in Indonesia. The impact of a large number of motorcycle certainly attracts the interest of the industry to produce two-wheeled automotive vehicles. The piston is part of the engine that functions as a compression barrier in the combustion chamber, the piston material is aluminum alloy. Therefore, research was carried out on making pistons with investment casting methods, physical and mechanical patterns from 3D printers on pistons. This research starts from drawing the piston using CAD (computer-aided design), making a printed pattern from a 3D Printer machine with PLA (polylactide acid) material. The mold pattern is coated with a mixture of gypsum cement and silica powder. The casting process with a pouring temperature of 750ᵒC and a mold temperature of 200 ᵒC, 250 ᵒC, 300 ᵒC, 350 ᵒC, and 400 ᵒC. The results showed the largest grain size at a mold temperature of 400ᵒC. The highest hardness at 200 ᵒC mold temperature is 47.00 HRB and the lowest hardness at 400 ᵒC mold temperature is 40.56 HRB. The higher the temperature of the mold used, the level of porosity of a material will decrease. This is due to the temperature difference when pouring the molten metal and the lower mold temperature. This makes the metal solidification time longer. The higher the mold temperature, the slower the solidification time, the larger the grain structure, and the decreased hardness.